P‐26: A New Modulable Integrated Multi‐Function Scan Driver for High‐Resolution AMOLED Display with LTPS TFTs. Issue 1 (29th May 2019) - Su, Yue; Geng, Di; Ji, Hansai; Zhang, Xia; Yu, Chaowei; Xu, Xiangyang; Takatori, Kenichi; Li, Ling; Liu, Ming
Abstract : We proposed a modulable integrated multi‐function scan driver for active‐matrix organic light‐emitting diode (AMOLED) display based on low‐temperature‐poly‐Si thin‐film transistors (LTPS TFTs). The proposed circuit provides dual outputs, the pulse width and time interval of which can be modulated, which is expected to be applied in high resolution AMOLED display.